Implementation of Problem Based Learning Module to Improve Students’ Interest in Physics Learning - A Halim; Adlim Adlim; Izkar Hadiya; Eviza Nurfadilla (Proceedings of AICS - Social Sciences, 2017)
This study aims to determine the effectiveness of the module that have been developed to improve the student's interest in learning, the advantages and disadvantages of the module, and the implementation of module for learning. The method of this research is Research and Development. The research population is science students class X in Senior High School 1 Peusangan, and sample group which determined by random technique is science student class X-1. The collected data are data of module assessment by teaching materials expert; media expert; and the teacher, data of student interest before and after learning with module, student’s response about the module, and teacher interview. The research instruments are the module assessment sheet for teaching materials expert; media expert; and the teacher, the student’s interest in learning questionnaire, questionnaire for student response, and the interview guidelines for teacher. The module effectiveness is determined with statistical test t correlated to average gain student interest before and after learning with module. The results showed significance difference between students' interest before and after is 41.30 % and students’ positive response about module is 73.43%. Analysis of the strengths and weaknesses of the module is obtained that module can create active learning for students with a scientific approach, but the participation of the teacher and completely facilities determine the learning process.